The dynamics of risk in transition: Beta, behavior, and information in Indonesia’s post-crisis stock market - Kaluge, David; Hascaryani, Tyas Danarti; Angraeni, Puspita Wahyu; Kaluge, Agapitus Hendrikus (Asian Economic and Financial Review, 2025)
This study investigates how sectoral beta dynamics, investor behavior, and informational asymmetry shape equity returns in Indonesia’s post-crisis capital market, characterized by volatility, retail dominance, and structural transitions. Employing panel regression across eleven sectors (2018–2025), we trace risk–return patterns over three regimes: pre-COVID, pandemic, and post-COVID recovery. Results reveal consistently positive and significant betas, yet crisis periods generate anomalies: low-beta sectors such as Agriculture and Property outperform high-beta counterparts. This divergence from classical CAPM expectations highlights the influence of retail herding and informational homogeneity. By integrating CAPM with behavioral finance and market microstructure perspectives, we construct a hybrid lens that captures both systematic risk and market psychology. The study contributes to ASEAN-focused scholarship in three ways. First, it empirically maps how sectoral betas adjust to regime shifts in a transitional economy. Second, it explains anomalous market movements through behavioral and informational mechanisms, advancing beyond traditional CAPM reasoning. Third, it offers policy-relevant insights by proposing a behavior-adjusted beta framework with implications for financial governance, investor literacy, and adaptive risk modeling. These findings underscore that equity pricing in emerging markets is shaped as much by psychology and information flows as by systematic risk, carrying lessons for Indonesia and comparable ASEAN economies.